The role of hypothermic machine perfusion in selecting renal grafts with advanced histological score. Issue 9 (22nd May 2022) - Ruberto, Franco; Lai, Quirino; Piazzolla, Mario; Brisciani, Matteo; Pretagostini, Renzo; Garofalo, Manuela; Giovanardi, Francesco; Nudo, Francesco; Poli, Luca; Zullino, Veronica; Santopietro, Pietro; Rossi, Massimo; et al.
Abstract: Background: Few studies explored the role of hypothermic machine perfusion (HMP) in the sub‐group of non‐standard renal grafts with a biopsy‐proven advanced histological impairment. This study aimed to investigate the role of HMP in grafts with a Karpinski Score >3 in terms of the need for dialysis, creatinine reduction ratio at day‐7 (CRR7), and 3‐year graft survival. Methods: Twenty‐three perfused grafts with Karpinski Score >3 evaluated between November 2017 and December 2018 were retrospectively analyzed and compared with a control group of 32 non‐perfused grafts transplanted between January 2014 and October 2017. Results: After transplantation, perfused grafts had fewer cases requiring dialysis (8.7% vs. 34.4%; p  = 0.051), a better reduction in serum creatinine (median at 7 days: 2.2 vs. 4.3 mg/dl; p  = 0.045), and shorter length of hospital stay (median 11 vs. 15 days; p  = 0.01). Three‐year death‐censored graft survival was better in the perfused cases (91.3% vs. 77.0%; p  = 0.16). In perfused grafts, initial renal resistance (RR) had the best predictive value for renal function recovery after the first week, as defined by CRR7 ≤ 70% (AUC = 0.83; p  = 0.02). A cut‐off value of 0.5 mm Hg/ml/min showed a sensitivity of 82.4%, a specificity of 83.3%, and diagnostic odds ratio = 23.4. After dividing the entire population into a Low‐RR ( n  = 8) and a High‐RR Group ( n  = 15), more cases with CRR7 ≤ 70% were reported in the latter group (86.7 vs. 13.3%; p  = 0.03). Conclusion: HMP yielded promising results in kidneys with Karpinski Score >3. Initial RR should be of interest in selecting non‐standard organs for single kidney transplantation even in impaired histology. Abstract : Few studies explored the role of Hypothermic Machine Perfusion (HMP) in the sub‐group of non‐standard renal grafts with a biopsy‐proven advanced histological impairment used for a single kidney transplantation. Twenty‐three perfused grafts with Karpinski Score >3 evaluated between November 2017 and December 2018 were retrospectively analyzed and compared with a control group of 32 non‐perfused grafts transplanted between January 2014 and October 2017. After transplantation, perfused grafts had fewer cases requiring dialysis, a better reduction in serum creatinine, shorter length of hospital stay, and better 3‐year death‐censored graft survivals. Initial renal resistance (RR) during perfusion showed promising results in selecting non‐standard organs for single kidney transplantation even in impaired histology.